MATCHED UNRELATED DONOR (MUD) PROGRAM FOR HEMATOPOIETIC STEM CELL TRANSPLANTATION IN SAUDI ARABIA. - Wishah, Husam; Hussain, Abeer (Oncology Nursing Forum, 2026)
Significance & Background: Matched unrelated donor (MUD) transplantation is a critical therapeutic option for patients with hematologic malignancies and bone marrow failure syndromes who lack suitable family donors. In regions such as Saudi Arabia, limited donor availability presents a significant barrier to timely transplantation, often delaying treatment and impacting outcomes. Purpose: To establish and operationalize a coordinated MUD transplantation program that improves access to life-saving therapies for patients without matched family donors, by integrating international donor registries, streamlining donor identification processes, and enhancing multidisciplinary collaboration across the transplant continuum. Interventions: A comprehensive MUD program was launched in 2016, with the first transplant performed in 2017. The program emphasizes coordinated care and patient navigation, leveraging international registries such as the National Marrow Donor Program (NMDP) and the World Marrow Donor Association (WMDA). It incorporates advanced HLA-matching technologies and multidisciplinary teamwork to streamline donor identification and transplant preparation. The donor database currently includes over 75,000 individuals. Results: To date, the program has facilitated approximately 200 successful unrelated donor transplants, serving patients across a wide age range and disease spectrum. Coordination among transplant teams, registry liaisons, and laboratory services has enabled efficient case management and timely intervention. Clinical outcome data, including engraftment success and one-year survival rates, are currently being analyzed and will be reported in future updates. Discussion: This initiative demonstrates the value of coordinated care and navigation in overcoming systemic barriers to transplantation. It has strengthened institutional capacity by improving communication pathways, standardizing protocols, and providing training for staff involved in transplant coordination. Future directions include expanding local donor recruitment to build a national registry, integrating real-time data systems to optimize matching algorithms, and conducting research to refine transplant protocols. The program offers a scalable model for improving access to complex therapies in resource-constrained environments.